ANALISIS MODAL KERJA DAN TINGKAT PROFITABILITAS (Pada PT. Bara Jaya Internasional Tbk Pada Tahun 2013-2017) - Danna Solihin, Marlina, Mardiana, (EKONOMIA, 2020)
Working capital is very important for companies, because companies always need working capital to finance their daily operations. The purpose of this study is to find out and analyze working capital as measured by working capital turnover and profitability as measured by return on investment at PT. Bara Jaya Internasional Tbk in 2013-2017 was higher or lower compared to the industry average of mining companies listing on the IDX.The research method used in this study focused on PT. Bara Jaya Internasional Tbk which focuses on financial statements, which consist of balance sheet and profit / loss report. The report is used to analyze working capital and the level of profitability measured using working capital turnover and return on investment (ROI).Working capital turnover in 2013 amounted to 5 times, in 2014 amounted to 1 time, in 2015 amounted to 0.2 times, in 2016 amounting to (0.1) times and in 2017 (0.1) times. The return on investment in 2013 was 0.9%, in 2014 amounted to 3%, 2015 was (9%), 2016 was (18%), and 2017 was (30%).The conclusion of this study is that working capital as measured by working capital turnover and the level of profitability as measured by return on investment at PT. Bara Jaya Internasional Tbk in 2013-2017 was lower than the industry average of working capital turnover of mining companies listed on the IDX and lower profitability compared to the industry average return on investment of mining companies listing on the IDX.